Formulation of Ketorolac Tromethamine for Controlled Release in Gastrointestinal and Colonic Delivery System - Hossain, Md. Amzad; Shill, Swapon Kumar; Khan, Shakhawat Hasan; Hossen, S. M. Moazzem; Uddin, Mohammad Nasir (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
A suitable matrix system of ketorolac tromethamine (KTR) formulation has been developed with the aim of increasing the contact time, achieving controlled release, reducing the frequency of administration, improving patient compliance. In this concern an enteric-coated KTR matrix tablet intended for specific delivery of drugs to the colon by combining the use of a time dependent core with a pH-sensitive film coating. Eudragit L100, with a threshold pH 7, was selected as coating material.Â New formulation is proved to be noble as to KTR delivery through both gastrointestinal and colonic system. New formulation is considered to reduce gastrointestinal side effects and achieve high local drug concentration at the afflicted site in the gastro-intestine and colon.Â